Perkaitan antara ayat 'itab dengan Ijtihad Rasulullah S.A.W. - Latifah Abdul Majid,; Mohd Nasir Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Muslim religious scholars differ in their opinions on the possibility of Muhammad’s ijtihÉd. Some of them believe that the ijtihÉd of Muhammad has taken place based on the direction from Allah to him in the forms of revelation to admonish his ijtihÉd. These different opinions are based on certain verses in the Koran and the Prophetic traditions. This study is to demonstrate the relationship between the admonitory verses in the Koran and the ijtihÉd of Muhammad. This study analyzes the admonitory verses by using the document analysis techniques. Finally, this research has successfully established the relationship between Muhammad’s ijtihÉd and the admonitory verses in the Koran.